Managing climate change risks and creating stakeholders' value via sustainability-focused B2B brand strategies - Khan, Huda; Gupta, Shaphali; Kumar, V.; Kumar, Binay (Elsevier, 2023)
As climate change poses substantial risks to society, businesses may expect that if they are responsive to climate change risks and adopt sustainable practices, stakeholders will embrace them. While as a consumer, one may buy from firms that show sensitivity to climate change and sustainability practices; however, when it comes to investing, they may behave the opposite. Scholarly research has predominantly examined the sustainability crisis and its implications in B2C settings. However, the issue is under-researched and more pertinent to B2B firms' practices as climate change is largely affected by the adopted industrial practices in the value chain and manufacturing process, which may not be environmentally friendly. In B2B firms, it is a complex scenario given that several value chain partners and intermediaries are involved, and their practices need to be aligned and integrated with the firm's sustainable development agenda. This tension naturally raises a question, i.e., what strategies B2B firms should adopt to generate stakeholders' value in view of the critical climate change risks? In attempting to resolve this pertinent challenge, our study provides a framework linking climate change risks to the firm's brand strategy, customer engagement, and, finally, to stakeholders' value. In developing our framework, we consider key contingency factors related to the firm, customer, and country. We also provide managerial guidance for B2B firms in mitigating the direct and indirect effects of the climate crisis and suggest directions for extending research on climate change risks and sustainability practices.
Keywords: Climate change risks; Grand challenge; Brand positioning; Value proposition; Customer engagement; Stakeholders' value; Sustainability; Crisis